2015
DOI: 10.1186/s12964-015-0114-x
|View full text |Cite
|
Sign up to set email alerts
|

L- and D-lactate enhance DNA repair and modulate the resistance of cervical carcinoma cells to anticancer drugs via histone deacetylase inhibition and hydroxycarboxylic acid receptor 1 activation

Abstract: BackgroundThe consideration of lactate as an active metabolite is a newly emerging and attractive concept. Recently, lactate has been reported to regulate gene transcription via the inhibition of histone deacetylases (HDACs) and survival of cancer cells via hydroxycarboxylic acid receptor 1 (HCAR1). This study examined the role of L- and D-lactate in the DNA damage response in cervical cancer cells.MethodsThree cervical cancer cell lines were examined: HeLa, Ca Ski and C33A. The inhibitory activity of lactate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 34 publications
5
135
0
1
Order By: Relevance
“…An interplay between tumor metabolites and epigenetic landscape has recently emerged, indicating that metabolism is closely associated with altered epigenetic landscape in cancer cells [32,33]. Indeed, lactate was suggested as modulating epigenetic mechanisms, namely, reduction of HDAC class I and II activity in colorectal and cervical cancer models [17,18]. Because class III/sirtuins' activity is NAD + -dependent and considering the high glycolytic rate of RCC cells and high lactate levels in the tumor microenvironment, a decrease in NAD + /NADH is expected, entailing SIRT activity inhibition [7,34].…”
Section: Discussionmentioning
confidence: 99%
“…An interplay between tumor metabolites and epigenetic landscape has recently emerged, indicating that metabolism is closely associated with altered epigenetic landscape in cancer cells [32,33]. Indeed, lactate was suggested as modulating epigenetic mechanisms, namely, reduction of HDAC class I and II activity in colorectal and cervical cancer models [17,18]. Because class III/sirtuins' activity is NAD + -dependent and considering the high glycolytic rate of RCC cells and high lactate levels in the tumor microenvironment, a decrease in NAD + /NADH is expected, entailing SIRT activity inhibition [7,34].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study evidenced that hCG increased protein expression of LH receptor mRNA binding protein (LRBP) and activated ERK signaling to regulate LHR mRNA translation in rat granulosa cells and ovaries (Nair and Menon, ; Menon et al, ). Treatment of lactate (10 and 20 mM) is able to increase the ERK phosphorylation in 5 min (Wagner et al, ). Matzkin et al () also demonstrated that ERK pathway regulates testosterone synthesis in Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, an accretion of lactate may promote resistance to radiation and lead to chemoresistance [151]. Wagner et al reveal that lactate can modulate cellular DNA damage repair processes in the uterine cervix, leading to the resistance of cervical cancer cells to anticancer therapy [152]. Since animals receiving chemotherapy or radiotherapy exhibit a reduction in lactate [153], checking this metabolite in human cancers might be used to predict therapeutic responses.…”
Section: Lactate Facilitates Cancer Developmentmentioning
confidence: 99%